Air Filtration in the Free Molecular Flow Regime: A Review of High-Efficiency Particulate Air Filters Based on Carbon Nanotubes - Li, Peng; Wang, Chunya; Zhang, Yingying; Wei, Fei (Small (Weinheim an der Bergstrasse, Germany), 2014)
Air filtration in the free molecular flow (FMF) regime is important and challenging because a higher filtration efficiency and lower pressure drop are obtained when the fiber diameter is smaller than the gas mean free path in the FMF regime. In previous studies, FMF conditions have been obtained by increasing the gas mean free path through reducing the pressure and increasing the temperature. In the case of carbon nanotubes (CNTs) with nanoscale diameters, it is possible to filtrate in the FMF regime under normal conditions. This paper reviews recent progress in theoretical and experimental studies of air filtration in the FMF regime. Typical structure models of high‐efficiency particulate (HEPA) air filters based on CNTs are introduced. The pressure drop in air filters operated in the FMF regime is less than that predicted by the conventional air filtration theory. The thinnest HEPA filters fabricated from single‐walled CNT films have an extremely low pressure drop. CNT air filters with a gradient nanostructure are shown to give a much better filtration performance in dynamic filtration. CNT air filters with a hierarchical structure and an agglomerated CNT fluidized bed air filter are also introduced. Finally, the challenges and opportunities for the application of CNTs in air filtration are discussed. Free molecular flow air filtration based on carbon nanotube air filters – from theoretical modeling to structure design.